Effectiveness of meaningful occupation interventions for people living with dementia in residential aged care: a systematic review. (December 2016) - Travers, Catherine; Brooks, Deborah; Hines, Sonia; O'Reilly, Maria; McMaster, Mitchell; He, Wei; MacAndrew, Margaret; Fielding, Elaine; Karlsson, Lina; Beattie, Elizabeth
EXECUTIVE SUMMARY: Background: The ability to participate in valued activities, whether for work, leisure or family, is an important aspect of personal identity. In dementia, progressive memory loss means that abilities developed over a lifetime begin to be lost as well, contributing to the loss of self and identity. Some studies have reported that activities or interventions tailored to be meaningful to the person with dementia (defined as any activity important to the individual) are more effective in addressing behavioral and psychological symptoms of dementia (BPSD) and improving quality of life (QoL) than those that are not so tailored. However, the effectiveness of individualizing interventions or activities for this population is not known. Objectives: In response to consumer feedback by the Consumer Dementia Research Network that this question ought to be addressed, this review was undertaken, the aim of which was to determine the effectiveness of meaningful occupation interventions for people living with dementia in residential aged care facilities (RACFs). Inclusion criteria: Types of participants People living with dementia in RACFs (nursing homes). Types of intervention(s)/phenomena of interest Any intervention that was individualized to be meaningful to the participant, versus any active control condition or usual care. Types of studies Experimental and observational studies. Types of outcomes : Quality of life, BPSD (such as agitation, aggression, depression, wandering and apathy), mood, function, cognition and sleep. Search strategy: The search strategy aimed to identify both published and unpublished studies, with the following 12 databases extensively searched: PubMed, CINAHL, PsycINFO, ISI Web of Science, OTSeeker, Embase, Cochrane CENTRAL, clinicaltrials.gov, Mednar, OpenSIGLE, New York Academy of Medicine Library Gray Literature Report, ProQuest Dissertations and Theses. The search strategy was limited to papers published in English between 2004 and January 31, 2015. Methodological quality: All studies were assessed independently by two reviewers for relevance, eligibility and methodological quality. Data extraction: Data from included papers were extracted using a standard data extraction tool. Data synthesis: Where possible, study results were pooled in statistical meta-analysis. Alternatively, results are presented in narrative and tabular form. Results: A total of 5274 citations were identified; after removal of duplicates, assessment for relevance and eligibility, 61 studies underwent critical appraisal. Thirty-four studies met the quality criteria and were included in a quantitative synthesis. A wide range of interventions were evaluated including individualized recreational activities (13 studies), reminiscence therapy (RT) (seven studies), music therapy interventions (six studies), training staff to develop individual care plans using person-centered care (PCC) or similar approaches (three studies), animal-assisted therapy (two studies), multi-sensory interventions (MSIs) (two studies) and social interaction (one study), all of which measured a number of different outcomes. Overall, and in spite of most studies being small-scale and of relatively brief duration, all interventions with the exception of Snoezelen therapy (a MSI) reported some benefits for people with dementia living in RACFs. The most frequently reported benefits were reductions in agitation (the most frequently assessed outcome), passivity and depression, improved QoL and increases in pleasure and interest. However, the majority of studies generally implemented the intervention, whether it was individualized activities, music or RT or other, in conjunction with one-to-one social interaction, and the relative importance of the intervention in comparison to one-to-one social contact for effectiveness cannot be determined from this review. Conclusion: Providing meaningful or individualized tailored activities for people with dementia living in RACFs appears to be effective for a range of behavioral and psychological symptoms. The strongest evidence was for individualized activities/recreational interventions for a range of BPSD; preferred music for agitation, depression and anxiety; and RT for mood and cognitive functioning. Insufficient evidence precluded making recommendations regarding animal-assisted (dog) therapy and training staff to develop individual care plans using PCC or similar approaches, while there was no good quality evidence to show that Snoezelen was effective for any outcome. What remains unclear, however, is whether any of these interventions is more effective than the provision of one-to-one social interaction.